Reactualization of Local History of Surakarta Chinese Ethnicity within the National Curriculum Framework - Riyadi; Djono (Universitas Negeri Surabaya, 2023)
Article focuses on the social history of the Chinese community in Surakarta in 20th century. Therefore, the discussion will emphasize various activities of daily life as a reflection of the social life of the Balong community. In this way we will be able to understand the history of social life and the changes that have occurred in that community. Chinese history in Surakarta has become a meaningful reality for students in Surakarta, but has not been summarized in the national curriculum, so much of the history learning carried out has not touched on this theme. This research will measure whether this sun can be summarized in the narrative of history learning at high school in Surakarta. The method used is the historical method. The results obtained from this research are that history learning can be applied by strengthening learning resources and textbooks, so that based on the existing material it develops into local themes which are summarized in history learning.